2017
DOI: 10.1016/j.hedp.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and analysis of time-gated monochromatic radiographs of cryogenic implosions on OMEGA

Abstract: Spherical polymer shells containing cryogenic DT ice layers have been imploded on the OMEGA Laser System and radiographed using Si backlighter targets (hν = 1.865 keV) driven with 20-ps IR pulses from the OMEGA EP Laser System. We report on a series of implosions in which the deuterium-tritium (DT) shell is imaged for a range of convergence ratios and in-flight aspect ratios. The shadows of the converging DT ice and polymer shells are recorded while the self-emission is minimized using a time-resolved (40-ps) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Improvements in our multi-physics codes now make this reanalysis a possibility. For example, Epstein et al [148] demonstrated that both short-pulse monoenergetic X-ray radiographs and self-emission x-ray images are well modeled by one-dimensional LILAC simulations. The legacy code used by the high-Z team before 2010 has been superseded by modern codes, and the high-Z experiments should be revisited with these tools.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in our multi-physics codes now make this reanalysis a possibility. For example, Epstein et al [148] demonstrated that both short-pulse monoenergetic X-ray radiographs and self-emission x-ray images are well modeled by one-dimensional LILAC simulations. The legacy code used by the high-Z team before 2010 has been superseded by modern codes, and the high-Z experiments should be revisited with these tools.…”
Section: Discussionmentioning
confidence: 99%